Implementing OLSR and Wireless VoIP as Low-Cost Infrastructure Telephony for Rural Area - Istas Pratomo; Asriadi N; Achmad Affandi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Communication is one of essential elements in this life, including the people who live at rural areas. However, telecommunications in rural area especially in Indonesia have many constraints like expensive infrastructure, difficult terrain and electrical problem. This led to a lot of areas that uncovered by telecommunication access. In this paper, we proposed a design and architecture of mobile wireless communication based on modified openWRT as a solution for low-cost communication and telephony infrastructure in rural areas. The design combines VoIP over mesh ad-hoc network as a potential solution for cheap calls and use modified embedded device to save electrical resources as a node to connect each other with multi hop transmissions. With this approach, we get many advantages such as high mobility, easy to use, scalable, low-cost implementation, and low power consumption. This paper presents the measurement result of performance to provide access telecommunication in several conditions. In addition, this paper also shows benchmarking results and lifetime of the node that we use in this prototype. The results show that our node can provide telecommunications access in terms of making calls with good quality using wireless LAN. To sum this up, The OpenVoice node is expected to contribute bridging digital divide in rural areas.